Investigation on Fabricating a Chicken Eggshells Powder Mold for Metal Casting - Numthong, Chaiwat; Rongchana, Supisara; Kunmaturos, Siraphaphar; Phattanaphibul, Thittikorn (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 4 (2021): October-December 2021DO - 10.14456/nujst.2021.32, 2021)
Sand casting is one of the metal casting techniques that is widely used in many applications. Besides a problem on surface quality of the casting from sand mold, sand extraction from places also gives serious environmental impact. Instead of using sand, a less environmental impact material has been considered. In this study, chicken eggshells waste is investigated for applying in metal casting process. The chicken eggshells waste is cleaned, air-dried and crushed into powder form. Bentonite and water are used to help cavity formation. A design of experiment was conducted to determine a suitable composition that provided the durable mold. Results illustrated that the specimens prepared from eggshells powder mixed with bentonite 10 wt% and water 16 wt% of eggshells powder, provided the highest ultimate compressive strength of 27.05±1.17MPa. In addition, the surface roughness of the castings was 5.86um, lying lower than the normal range of the sand casting process. With these investigated properties, the results presented the potential of using the chicken eggshells waste in this application. Keywords: Chicken, Waste, Eggshells, Metal Casting, Mold